2015
DOI: 10.1089/end.2014.0714
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Makes Pleasure: A Preliminary Study of Increasing Irrigation Pressure of Flexible Cystoscopy Improves Male Patient Comfort by an Easy Way

Abstract: Achieving higher irrigation pressure for flexible cystoscopy by adjusting the height of irrigation solution bag improves male patients' comfort. It is recommended for male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This finding was not universal, as statistically significant differences were not observed at all assessed time points, or in all examined groups. However, there is a trend to worse pain scoring during the first cystoscopy and in younger men, which is also described by other authors [35, 2022]. While the aim of our study was to optimise local anaesthesia for cystoscopy, these findings are clinically useless despite their relevance.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This finding was not universal, as statistically significant differences were not observed at all assessed time points, or in all examined groups. However, there is a trend to worse pain scoring during the first cystoscopy and in younger men, which is also described by other authors [35, 2022]. While the aim of our study was to optimise local anaesthesia for cystoscopy, these findings are clinically useless despite their relevance.…”
Section: Discussionsupporting
confidence: 64%
“…Zhang et al recently improved this technique. They confirmed that higher irrigation pressure is associated with less discomfort during cystoscopy and proposed to raise the irrigation solution bag and adjust the height in order to easily improve patients’ satisfaction [22]. Apart from technical tips and tricks, Yeo et al found that listening to classical music during rigid cystoscopy is a simple, economical and effective means of enhancing patient comfort and reducing feelings of pain, anxiety, and dissatisfaction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the technological advances in modern flexible cystoscopes, we think that the irrigation pressure would also play an important role in patient tolerance. Zhang et al [17] demonstrated that achieving a higher irrigation pressure for flexible cystoscopy improved male patient comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, researchers have conducted many trials to seek potentially adjuvant therapy to alleviate patient pain during cystoscopy, especially for male patients. The proposed nonpharmacological methods included increasing irrigation pressure (3)(4)(5), delaying the instillation time of topical anesthetics in the urethra (6)(7)(8), allowing patients to watch the procedure process (9)(10)(11), listening to music (12,13), hand-holding (14), urinating during FC (15), and virtual reality distraction (16). All these interventions are practical, inexpensive, and harmless.…”
Section: Introductionmentioning
confidence: 99%